Improvement of large power system with facts devices placement to maxim-IZE the system load ability - L. Bekri, O; Mekri, F (International Journal of Engineering and Technology, 2018)
Voltage instabilities and/or collapses have been recognized as one of the major causes of power system blackouts. The main objective of this paper is to provide some solutions to prevent large power systems from voltage collapse. The FACTS (Flexible AC Transmission Sys-tems) devices placement gives new opportunities for enhancing voltage stability. The calculation of the loadability point is based on the con-tinuation power flow technique (CPF) to choosing the optimal placement of STATCOM (Static Synchronous Compensator) in order to improve voltage stability by increasing the loading parameter, maintaining bus voltages at desired level and minimizing losses in a power system network.A 39-bus New England power system is chosen as test case in order to illustrate this approach. The obtained results show the efficiency of the proposed method for the planning of the Static Synchronous Compensator optimal placement and the voltage stability enhancement.Â Â